A multiple case study on the residential interior space utilization among selected college students from middle class intergenerational households in Metro Manila - Asilo, Heryka C. (College of Home Economics, University of the Philippines Diliman, 2019)
Given that every member of the family may have varied needs when it comes to their personal and shared spaces, especially in an intergenerational household, the study attempted to analyze how the residential interior space utilization of college students who belong to intergenerational households is affected by this. A total of three (3) college students from Metro Manila, who belong to intergenerational households with 8-10 members, were purposively selected as respondents for this multiple case study. For the data collection, an observation guide, interview guide, measuring tape, and digital camera were used. The Theoretical Framework of the study was anchored on the theory of Proxemics. Based on the data gathered and analysis conducted, the residential interior spaces of the respondents are all semi-fixed feature space, where boundaries of spaces and the activities are more flexible or movable, to accommodate the different spatial needs and activities of all family members. Filipino values, such as having strong family ties, paggalang (respect) and pakikisama (comradeship), manifest in the interior space utilization of the respondents. Socioeconomic status is the main constraint from solving the most pressing problems in the space, such as not enough space and the lack of storage. For future studies, other researchers could investigate respondents from rural communities since they may have different dynamics and practices compared to those from Metro Manila. The researcher also recommends getting input from other members of the family to gain more in-depth understanding of the families' interior space utilization.